PELATIHAN PENYUSUNAN PERANGKAT PEMBELAJARAN BERBASIS REALISTIC MATHEMATICS EDUCATION (RME) BAGI GURU DI KECAMATAN TEHORU DAN TELUTIH - Mananggel, Marlin Blandy; Mataheru, Wilmintjie; Salamor, Reinhard (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2022)
Mathematics learning is currently still focused on material goals, which means that students passively accept mathematical knowledge as "goods" which are transferred by the teacher. The teacher as an important component of the learning process requires learning facilities or media that support the learning. The purpose of this program is to train teachers in preparing learning tools based on realistic mathematics education (RME). This program was implemented in SMA Negeri 9 Maluku Tengah, Tehoru District, Maluku Tengah Regency and elementary and junior high school teachers throughout Tehoru-Telutih District as the target of the activity. This program is carried out in several stages, namely planning, implementation, evaluation and reflection. At the planning stage, coordination was carried out with the District Coordinator of Tehoru-Telutih and partners. The instruments used were a survey of prior knowledge and a participant satisfaction questionnaire. At the implementation stage, initial surveys, training and demonstrations were carried out. Based on the results of joint evaluation and reflection between the implementers and partner teachers, this PPM program is considered to have run very well, there are only suggestions for improvement, namely additional practice time which should be longer. This program is expected to increase partner teachers' mastery of RME-based learning tools and will continue and develop not only in Tehoru-Telutih District, but also for teachers throughout Maluku Tengah Regency